2021
DOI: 10.1016/j.repc.2021.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Facemasks during aerobic exercise: Implications for cardiac rehabilitation programs during the Covid-19 pandemic

Abstract: Resumo Introdução e objetivos: Durante a pandemia COVID-19 a utilização de máscaras faciais, incluindo durante o exercício terapêutico, faz parte das medidas de segurança adotadas. Este facto originou preocupação a nível das unidades de reabilitação cardíaca, uma vez que as máscaras faciais podem promover efeitos deletérios na capacidade de exercício. Este estudo avaliou o impacto da utilização das máscaras faciais durante o treino aeróbio em passadeira. Métodos: Doze profissionais de saú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…In this regard, and as explored by Pimenta et al, several studies have been undertaken to try to address this issue. 3 , 4 , 6 , 7 , 8 Notably, however, and as discussed in the current report, there has been some divergence of results on the impact of face masks in individuals doing exercise. 3 , 7 , 8 , 9 Although some studies have shown differences in terms of ventilatory parameters and exercise capacity, 4 , 6 a review by Hopkins et al .…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…In this regard, and as explored by Pimenta et al, several studies have been undertaken to try to address this issue. 3 , 4 , 6 , 7 , 8 Notably, however, and as discussed in the current report, there has been some divergence of results on the impact of face masks in individuals doing exercise. 3 , 7 , 8 , 9 Although some studies have shown differences in terms of ventilatory parameters and exercise capacity, 4 , 6 a review by Hopkins et al .…”
mentioning
confidence: 58%
“… 3 , 4 , 6 , 7 , 8 Notably, however, and as discussed in the current report, there has been some divergence of results on the impact of face masks in individuals doing exercise. 3 , 7 , 8 , 9 Although some studies have shown differences in terms of ventilatory parameters and exercise capacity, 4 , 6 a review by Hopkins et al . showed that while the use of face masks during exercise may be associated with increased levels of dyspnea and effort perception, its effects in physiological parameters such as blood gases and work of breathing tended to be relatively small.…”
mentioning
confidence: 58%
See 3 more Smart Citations